Pengaruh model problem based learning berbasis pembelajaran berdiferensiasi pada materi keanekaragaman hayati terhadap rasa ingin tahu peserta didik - Septianawati, Laili Khusnul; Atmojo, Idam Ragil Widianto (Didaktika Dwija Indria, 2026)
This study aimed to examine the significant effect of the Problem Based Learning model based on differentiated instruction on students' curiosity in the topic of biodiversity. A quantitative approach with an experimental method was employed. The research design used was a pretest posttest control group design. Data were collected using a curiosity questionnaire administered before and after the treatment. The sample was selected using a probability sampling technique with the cluster random sampling method. The implementation of the Problem Based Learning  model, adapted through differentiated instruction strategies based on students’ learning styles, specifically enhanced curiosity particularly among students with a visual learning style, who achieved the highest curiosity score of 83.4%. The results of the independent samples t-test showed a significance value of less than 0.001, indicating a statistically significant effect. These findings indicate that the integration of the PBL model based on differentiated instruction in the biodiversity topic has a positive and significant impact on students’ curiosity.